Unsur 5W+1H Dalam Caption Konten Instagram Surveyor.Id - Vatmaya Mutiara; Ade Haryani (Jurnalistik dan Media, 2024)
Content creation trough social media belonged to certain institution has been prevalent for the last several years. This study aims to analyze the application of the 5W1H framework (Who, What, When, Where, Why, How) in Instagram captions of surveyor.id during the period of March 24 to May 23, 2024. By implementing a descriptive method and content analysis, this research examined the 13 most popular Instagram posts. The findings revealed that a majority of the content successfully incorporated the 5W1H elements, particularly what and who. However, the utilization of where and when elements could be further enhanced. Consistent application of the 5W1H framework can facilitate audience comprehension. In conclusion, this research underscores the significance of adhering to the 5W1H framework in crafting effective Instagram content. Companies should prioritize consistency inthe implementation of all 5W1H elements, especially for informative content, to provide a clearer understanding for the audience. Keywords: caption content, Instagram, 5W+1H